MORPHOLOGICAL AND FUNCTIONAL MODIFICATIONS DURING THE PROCESS OF AGEING: CHARACTERISTICS AND BENEFITS OF PHYSICAL ACTIVITY - Paola Vago; Nicola Lovecchio (Annales Kinesiologiae, 2015)
Ageing is a slow but dynamic process, which involves many internal and external influences. It is a complex multifactorial phenomenon characterized by progressive physiological, genetic, endocrinological and molecular changes, responsible for the increased risk of morbidity and death.